Students’ Metacognitive Strategy Pattern in English Academic Writing Learning Using Zoom - Euis Meinawati; Prapti Wigati Purwaningrum; Herlin Widasiwi Setianingrum; Sufi Alawiyah; Lia Nurmalia; Nurmala Dewi; Meiva Eka Sri Sulistyawati; Viviana Lisma Lestari (STAI Hubbulwathan Duri, 2021)
Students have a different pattern in using the learning strategy. It is seen in their activity when they do the writing. The objective of this research was to observe the students’ pattern using metacognitive strategy in English Academic Writing learning through an online zoom application. The method used descriptive qualitative research. The data is taken from observation and survey from 20 participants who got the English academic writing subject in 2019/2020 academic years at English Program Study Universitas Bina Sarana Informatika. Analysis procedures include observation of activity patterns, identifying learning strategy patterns, categorizing, and strategy learning pattern analysis. The results showed that the students used metacognitive strategy in the academic writing process with different patterns. It can see from activity steps of the metacognitive strategy that is implemented in the class. Students’ activity pattern is planning, identifying, correcting errors, revising, rereading, monitoring, and evaluating. Metacognitive strategies had used by students to consciously control the writing activity because each segment of one’s stored world knowledge help students to create the story. The study's implication is managing students’ activity patterns when the teacher used the strategy learning. It has to be appropriate to students’ needs.